SONGKOK RECCA SEBAGAI IDENTITAS BUDAYA (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2021)
The meaning of Songkok Recca' as a cultural identity. This study aims to determine how the perception of the people of Bone Regency regarding the meaning of Songkok Recca' so that it becomes the characteristics, characteristics, and cultural identity of Bone Regency. This type of research is using qualitative research with qualitative approach research, namely phenomenology. The source of this research data is the community Bone Regency, which is classified specifically from government circles in this case the General Secretary of the Bone Regency Culture Service, community leaders, traditional stakeholders, cultural experts, Songkok Recca' craftsmen, and youth leaders. The method used in digging up information and looking for data is by means of observation, interviews, and documentation of informants. Meanwhile, data processing and data analysis techniques were carried out through four stages, namely: data collection stage, data reduction, data presentation, and conclusion drawing.